Proses Pembuatan Santan Cair Dari Kernel Kelapa Sawit Dengan Penambahan Penstabil Mono-Diacyl Glycerol (M-DAG) - Dimas Syaiful Ansori; Ngatirah Ngatirah; Dina Mardhatilah (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2026)
This study developed an innovation in producing coconut milk from oil palm kernel with the addition of the stabilizer M-DAG. The research aimed to determine the effect of the kernel-to-water ratio and the M-DAG concentration on the physical and chemical properties of the resulting kernel milk, and to identify the best combination that meets the Indonesian National Standard (SNI) and is most preferred by panelists. The experiment used Randomized Complete Block Design (RCBD) with two factors: the kernel-to-water ratio (1:1, 1:2, 1:3 w/w) and the M-DAG concentration (1%, 2%, 3%). The kernel milk was analyzed for fat content, viscosity, pH, free fatty acids, total solids, emulsion stability, peroxide value, and organoleptic characteristics (aroma, color, and taste). The results indicated that the kernel-to-water ratio significantly affected all tested parameters: fat content, viscosity, pH, free fatty acids, total solids, emulsion stability, peroxide value, and organoleptic characteristics. The concentration of M-DAG influenced most physicochemical properties, except for peroxide value and organoleptic attributes, which showed no significant differences. All samples exhibited the same level of organoleptic preference. The best kernel milk, which complied with the SNI standard, was produced with a kernel-to-water ratio of 1:1 (w/w) and 1% M-DAG. This sample had the following characteristics: pH of 6.01; total solids of 9.18%; fat content of 18.17%; free fatty acids of 0.17%; viscosity of 15.32 mPa.s; emulsion stability of 60.20%; and a peroxide value of 17.89 mEq/kg.